Analisa Ketepatan Jumlah Produksi Crude Palm Oil (CPO) dengan Fuzzy Inference System (STMIK Budi Darma, 2022)
Crude Palm Oil (CPO) is crude palm oil. This product is obtained from the extraction or compression process of the fruit flesh (mesocarp) of oil palm generally from the Elaeis guineensis species and has not been purified. The production of palm oil (CPO) at the right time and in the right amount is something that palm oil mill companies want. However, in determining the amount of CPO production in the future, it is not easy, especially when it is still using manual calculations so that it will experience difficulties in managing production figures. This study aims to help the factory determine the right number of numbers in producing CPO. The data processed were 12 data which were analyzed using the Mamdani Fuzzy logic method. This method will process input data in the form of order and stock data. Fuzzy logic is an effective solution to predict the instability of CPO production. The application of this fuzzy logic can reduce losses due to variance trends in the production and sales of CPO PT. Sawita. From the results of testing the 2021 data for 12 data, the percentage of similarity between manual data and system testing is 90% so that the results are acceptable.